Analisis Campur Kode pada Novel Berandal Bandung Karya I. A. A. Djiiwaraga - Arisma Nurohmah; Ita Kurnia; Rosani Fadila Anmaragis; Dewi Ma'rifatul Ghoiriyah (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This study analyzes code-mixing phenomena in the novel Berandal Bandung by I.A.A-Djiiwaraga using a qualitative descriptive approach. The research aims to identify forms and functions of code-mixing involving Sundanese and English languages within the Indonesian narrative context. Data collection was conducted through documentation study by reading, noting, and classifying code-mixing instances throughout the 330-page novel. The analysis reveals that Sundanese code-mixing dominates with high frequency, particularly in pronouns (urang, maneh) and adjectives (kasep, geulis), while English code-mixing appears in specific contexts related to technology, business, and emotional expression. Code-mixing functions as: (1) ethnic and cultural identity markers, (2) group solidarity builders, (3) prestige and modernity symbols, (4) emotional expression tools, and (5) referential needs fulfillment. The findings demonstrate that code-mixing in modern literary works serves multidimensional functions reflecting linguistic dynamics, cultural identity, and contemporary social reality in multilingual Indonesian society.